Nub1 As A Prognostic Marker In Breast Cancer: A Retrospective, Integrated Genomic, Transcriptomic, And Protein Analysis. - K.L.Tan; F. Pezzella; A.Harris; O.Acuto (BMJ Journals, 2024)
Volume: 3 Supplement : 2